2012
DOI: 10.5194/bgd-9-11815-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of large above ground biomass variability in lowland forest ecosystems by airborne LiDAR

Abstract: Quantification of tropical forest Above Ground Biomass (AGB) over large areas as input for Reduced Emissions from Deforestation and forest Degradation (REDD+) projects and climate change models is challenging. This is the first study which attempts to estimate AGB and its variability across large areas of tropical lowland forests in Central Kalimantan (Indonesia) through correlating airborne Light Detection and Ranging (LiDAR) to forest inventory data. Two LiDAR height metrics were analysed and regressi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…Lidar scanning technologies send beams through the canopy and measure the forest structure (e.g., leaf and branch density as the emitted beams interact with them) (32). Hereby, the density of signals returned at a specific height may be comparable to the observed pattern of leaf area density across height (31). Knowledge on the heterogeneous crown structure of forests derived from this study can potentially enhance the interpretation of such remote sensing measurements.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lidar scanning technologies send beams through the canopy and measure the forest structure (e.g., leaf and branch density as the emitted beams interact with them) (32). Hereby, the density of signals returned at a specific height may be comparable to the observed pattern of leaf area density across height (31). Knowledge on the heterogeneous crown structure of forests derived from this study can potentially enhance the interpretation of such remote sensing measurements.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings provide important insights into the heterogeneous structure of forests that might be useful also for remote sensing of forests (28,31). Lidar scanning technologies send beams through the canopy and measure the forest structure (e.g., leaf and branch density as the emitted beams interact with them) (32).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hudak et al [45] used LiDAR measurements with significant differences in point densities and found out that different point densities do not affect AGB estimations if LiDAR measurements were independently analyzed. Previous studies revealed that the centroid height is an appropriate height parameter of the LiDAR point cloud to estimate AGB in tropical forests taking also the point distribution over the different vegetation layers into account [27][28][29]. It was therefore used in this study to estimate AGB and its changes.…”
Section: Biomass Estimationmentioning
confidence: 99%
“…Different point cloud statistics of the vegetation height and canopy cover were tested for their performance to predict AGB in peat swamp forests using linear, multiple linear and power functions. Appropriate parameters to estimate AGB were found to be relative height quartiles (r 2 = 0.71, RMSE = 115.2 t/ha or r 2 = 0.7, RMSE = 28.6 t/ha) [27,31] the AGB regression models can be improved by using the point density as input [29]. Multi-temporal LiDAR measurements offer tremendous potential for REDD+ requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation